Subcutaneous Granuloma Annulare: A Diagnostic Conundrum-Learning From Mistakes. - Pederiva, Federica; Paloni, Giulia; Berti, Irene (Pediatr Emerg Care, 2017)
Subcutaneous granuloma annulare is an inflammatory lesion occurring in otherwise healthy children. We present 3 pediatric patients with different diagnostic-therapeutic paths depending on the ward they were referred to. The lesions regress spontaneously, and medical or surgical treatments are generally not necessary.
Keywords: Arm; Child, Preschool; Connective Tissue Diseases; Diagnosis, Differential; Female; Granuloma Annulare; Humans; Infant; Leg; Male; Ultrasonography, Doppler, Color